An efficient process for sustainable and scalable hydrogen production from green ammonia. (December 2021) - Cha, Junyoung; Park, Yongha; Brigljević, Boris; Lee, Boreum; Lim, Dongjun; Lee, Taeho; Jeong, Hyangsoo; Kim, Yongmin; Sohn, Hyuntae; Mikulčić, Hrvoje; Lee, Kyung Moon; Nam, Dong Hoon; et al.
Abstract: This study comprehensively investigates hydrogen production from green ammonia reforming, including synthesis of catalysts, reactor development, process integration, and techno-economic analysis. In-house developed Ru/La–Al2 O3 pellet catalyst having perovskite structure showed high catalytic activity of 2827 h −1  at 450 °C and stability over 6700 h at 550 °C, exceeding the performance of the majority of powder catalysts reported in the literature. A scalable 12-faceted reactor adopting the as-produced catalyst was designed to enhance heat transfer, producing over 66 L min −1 of hydrogen with state-of-the-art ammonia reforming efficiency of 83.6 %. Near-zero CO2 emission of hydrogen extraction from green ammonia was demonstrated by-product gas recirculation as a combustion heat source. A techno-economic assessment was conducted for system scales from 10 kW to 10 MW, demonstrating the effect of reduced minimum hydrogen selling prices from 7.03 USD kg −1 at small modular scales to 3.98 USD kg −1 at larger industrial scales. Sensitivity analyses indicate that hydrogen selling prices may reduce even further (up to 50 %). The suggested hydrogen production route from green NH3 demonstrates superior CO2 reduction ranging from 78 % to 95 % in kg CO2 (kg H2 ) −1 compared to biomass gasification and steam methane reforming. These findings can be used as a basis for following economic and policy studies to further validate the effectiveness of the suggested system and process for H2 production from NH3 . Highlights: Experimental and techno-economic analyses of H2 from green NH3 are conducted. As-developed Ru pellet catalysts showed high activity of 2827 h −1  at 450 °C. Reforming efficiency of 83.6 % was achieved at 5 kWe scale with a COX free operation. Minimum H2 selling price of 4 USD kg −1 is expected at industrial scales >10 MW. CO2 emission can be reduced up to 95 %, compared to the conventional processes.